Toward Digital Alignment: IS/IT Strategy Development for a Non-Profit Foundation Using Ward & Peppard - Virdha Rahma Aulia; Fatharani Mazaya Agniya Putri; Mafda Khoirotul Fatha; Viviana Purba; Alfiansyah Adi Pranata (LKP KARYA PRIMA KURSUS, 2025)
This paper presents a strategic information systems (IS) and information technology (IT) planning for a prominent national non-profit organization, hereafter referred to as XYZ Foundation , using the Ward & Peppard methodology. Facing rapid technological advancements and evolving operational landscapes, XYZ Foundation seeks to enhance its digital capabilities, improve service delivery, and strengthen donor trust. The study details a comprehensive analysis of the organization's internal and external business environments, as well as its current IS/IT landscape. Key findings reveal challenges in system integration, IT human resource capacity, and the absence of a long-term technology roadmap. Based on a thorough gap analysis, strategic recommendations include the development of an integrated digital portal, automation of donation processes through fintech integration, implementation of blockchain for transparency, migration to cloud infrastructure, and significant investment in IT human resource development and governance. The proposed strategic roadmap outlines a phased implementation plan from 2025 to 2029, aiming to foster internal efficiency, expand social outreach, and build a robust, future-ready digital foundation.